Analysis of Risk Factors for Commercial Sex Workers and the Prevalence of the Human Immunodeficiency Virus (HIV) - Sajuni Widjaja; Winnie Nirmala Santosa; Dwi Martha Nur Aditya (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Human Immunodeficiency Virus (HIV) and Acquired Immunodeficiency Syndrome (AIDS) are one of the biggest health problems in the 21st century. HIV/AIDS cases continue to soar, one of which is due to the practice of prostitution because commercial sex workers (CSW) are a group at high risk of contracting HIV/AIDS. Dolly, the largest localization at Surabaya, has already been closed by the government to decrease the transmission of HIV. The research method is based on laboratory examination using the Rapid Test Immunochromatography method, with the subject of examination being women who live around Dolly localization. This method has the advantages of fast inspection time (only around 15-30 minutes), is easy to do, do not use special tools, and is quite sensitive. The number of women who were HIV positive was 1.4%, and the numbers who were HIV negative was 98.6%. The association between the risk variables for CSWs and HIV status was then determined using the Spearman correlation test. Statistical analyses revealed a significant relationship between CSW status and HIV prevalence with a significance value of 0.05 (p=0.025; CI=95%). Since the correlation coefficient is positive, a rise in CSWsâ€™ active status can also increase HIV prevalence.Â